Pemanfaatan Remote Sensing (RS) Untuk Mengetahui Kepadatan Penduduk di Desa Rumah Tiga, Kec Teluk Ambon, Kota Ambon - Siti Fiznawati Nazudin; Roberth Berthy Riry; Edward Gland Tetelepta (Jurnal Pendidikan Geografi Unpatti, 2025)
Population density is a strategic issue in spatial planning, particularly in areas experiencing rapid settlement growth, such as Rumah Tiga Village, Teluk Ambon. This study aims to estimate population density using remote sensing (RS) technology and geographical information systems (GIS). The method employed is a dasymetric mapping approach based on Google Earth Pro satellite imagery, with manual digitization of built-up areas and spatial analysis. The results show that the estimated population density using RS reaches 660.69 people/km², significantly higher than the official figure from BPS (334.84 people/km²) due to the focus on actual inhabited areas. Spatial validation was conducted using NDVI and NDBI indices, and it was overlaid/RW administrative data. This study concludes that RS is effective for estimating and mapping population distribution, and supports spatial data-based decision-making for sustainable village spatial planning.